Health Status Dynamics in Adolescents of Ukraine - T.V. Peresypkina (Zaslavsky O.Yu., 2014)
The paper presents the results of the health status analysis in adolescents of Ukraine for the period of 2001-2012. The data of for Medical Statistics Center of Ministry of Healthcare of Ukraine were used. The objective of this study - to assess the health status indices among adolescents of Ukraine, to follow-up the trends of its changes. A steady increase in the prevalence value, growth of which from 2001 to 2012, amounted to 42.0 %. For the analyzed period there have been registered changes in the patterns of the diseases. In 2012 the leading disorders in the structure of prevalence were respiratory diseases; digestive diseases; of osteomuscular system and connective tissue; of eye and adnexa oculi; endocrine system, nutritional and metabolic disturbances, diseases of the nervous and urogenital systems; of skin and subcutaneous tissues. The dynamics of changes of the parameter was estimated by the growth rate. The highest growth rate has been registered in such classes as: neoplasms, congenital anomalies; diseases of the circulatory system; of blood, blood-forming and respiratory organs. The data obtained should be used to develop targeted prevention programs and organizational decision to improve the quality of medical care, which should include priority researches, monitoring of health status and the factors shaping it, as well as the possibility of cross-sectoral cooperation.